Exploring different technical solutions of the interface between the hand, racket and the rim in wheelchair tennis - Koopman, J.; Berger, M.; Hoekstra, A.; de Groot, S. (Procedia Engineering, 2016)
Purpose: In wheelchair tennis propulsion of the wheelchair is different for both hands, since the athlete has to hold a tennis racket in one hand. Differences in propulsion technique, i.e. forces and timing, have been found between propelling the wheelchair with and without a racket in the hand [1]. Optimizing the coupling of the hand with the racket to the rim is expected to lead to performance improvement Therefore, the purpose of this study was to explore different technical solutions for the interface between the hand, racket and the rim in order to optimize propulsion technique during wheelchair tennis when holding a racket. Methods: A limited literature study was done on the interface between the hand, racket and the rim. Qualitative interviews were held with (sub)top Dutch tennis players and trainers to gain insight in their technique. Video analysis of training and tennis matches of (sub)top Dutch tennis players were made to acquire knowledge of the hand and racket positions. A list of requirements and several ideas were developed. Different prototypes of (a part of) a rim were 3d printed and tested in laboratory settings. Results: The literature study showed an increase of effectivity of propulsive force by creating a larger contact area and increased friction; different textures and/or materials can create an increased friction. The video analysis showed a variety of racket positions between players and within players at different speeds. Five different design components and the connections between them were explored: push rim, wheel, the tire, the hand and the racket. Prototypes with a larger contact area and/or different material showed higher isometric peak forces. Conclusion: This study shows different technical solutions for the interface between the hand, racket and the rim, which will improve propulsion technique during wheelchair tennis. The technical solutions are; different shape of the rim and/or using textures and/or materials with high friction coefficient on the rim and/or hand.